Defending childhood : keeping the promise of early education - Falk, Beverly (New York : Teachers College Press, 2012)
This book brings together a group of educators and scholars who offer insights about what we can do to defend childhood from societal challenges. The authors explain new findings from neuroscience and psychology, as well as emerging knowledge about the impact on child development of cultural and linguistic diversity, poverty, families and communities, and the media. Each chapter presents experiences and suggestions, from the perspectives of different disciplines, about what can be done to ensure that all children gain access to the supports they need for optimal physical, social, intellectual, and emotional development.
The science of early childhood development : lessons for teachers and caregivers / Todd A. Grindal, Christina Hinton, and Jack P. Shonkoff -- A tale of two schools : the promise of playful learning / Jessa Reed, Kathy Hirsh-Pasek, and Roberta M. Golinkoff -- Honoring the lives of all children : identity, culture, and language / Sonia Nieto -- Low-income families and young children's development and school success / Barbara Bowman and Aisha Ray -- Foreclosed childhoods : poverty, inequality, and discarding the young / Valerie Polakow -- r
Includes bibliographical references and index.
Keywords: Early childhood education -- United States; Child development -- United States